2016
DOI: 10.1136/bmjquality.u211816.w4748
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing clinical pharmacists to improve delivery of evidence-based care for depression and anxiety in primary care

Abstract: Access to mental health providers has become an increasingly common challenge for many patients with depression and anxiety disorders. Primary care providers often manage this gap in care and currently provide solo care without the assistance of other team members. In order to provide quality care that aligns with best practice, we developed a depression and anxiety disorder treatment pathway utilizing a multidisciplinary team based on each members' individual skill set, or skill-task alignment. The main chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Clinical pharmacists increased their skillset for treating depression and anxiety and enhanced their ability to make interventions with patients who are referred to them for other chronic disease state management (e.g. hypertension, chronic pain) [44]. Though pharmacists are trained in psychopharmacology, they lack formal MH intervention skills [29].…”
Section: Fig-1: Changing the Conversation About Mental Health (Mh) [1]mentioning
confidence: 99%
“…Clinical pharmacists increased their skillset for treating depression and anxiety and enhanced their ability to make interventions with patients who are referred to them for other chronic disease state management (e.g. hypertension, chronic pain) [44]. Though pharmacists are trained in psychopharmacology, they lack formal MH intervention skills [29].…”
Section: Fig-1: Changing the Conversation About Mental Health (Mh) [1]mentioning
confidence: 99%
“…Additionally, studies have indicated the impact of clinical pharmacists improving medication management of patients with mental health conditions in the primary care setting. [12][13][14][15][16][17] Therefore, it is critical to explore PCP's attitudes toward pharmacist-provided mental health medication support within the PCMH and the needs of PCPs in mental health management in the design of a new pharmacy service. PCMH pharmacy and psychiatry leadership within our academic medical center are exploring ways to help support the management of patients with mental health conditions, primarily around medication management and education.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to explore the gaps in service provision relating to medicines and determine whether a specialist pharmacy team could provide useful input for patients on the SMI register. In primary care, specialist input is uncommon, although some benefit has been demonstrated for depression and dementia10 11; however, involvement of specialist mental health pharmacists for SMI in a GP setting has not been explored.…”
Section: Introductionmentioning
confidence: 99%